The Influence of Flashcard on Students’ Ability to Use Present Tense in Writing at Primary School - Permata, Aura Dwi; Juniardi, Yudi; Baihaqi, Akhmad (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The main issue of this research is the low learning outcomes of students in English language learning, one of the factors behind this problem is the lack of learning innovations used. This research used flashcards as learning media to make students interested in learning English. This research used flashcards as media in learning simple present tense material  This research aimed to find out if there is a significant effect of flashcards on students’ simple present tense writing ability at SDN Rawu. To achieve that aim,  this research used quasi-experimental design. This study involved 64 students as the sample consisting 32 students in the experiment class and 32 students in the control class.  For data collection techniques, a pre-test was given to both classes at the first meeting and then the post-test at the last meeting. The result showed that the students in the experimental class obtained significantly higher scores than the control class. This is proven by the results of Paired Sample T-Test where the sig-2 tailed value was 0.00, while the alpha(a) was 0.05 showing that the sig. value is lower than 0.05 (0.00 < 0.05).  This demonstrates that the alternative hypothesis is accepted. It can be concluded that there is any significant influence of flashcards toward students’ writing abilities at SDN Rawu.